CP-158 Our experience with fampridine in patients with multiple sclerosis after 2 years of treatment. (24th March 2015) - Escolano Pueyo, A; Navarro, H; Perez, C; Sebastian, B; Seral, M; Abad, M
Abstract : Background: Fampridine is indicated for the improvement of walking in patients with multiple sclerosis (MS) (EDSS 4–7). Purpose: To assess the effectiveness, undesirable effects and adherence to fampridine. Material and methods: A 30-month retrospective study was conducted, including MS patients receiving fampridine 10 mg BID. Medical records were reviewed for data on Timed 25-Foot Walk (T25FW) and 12-item MS walking scale (MSWS-12), from baseline over a 24-month period (screening at baseline, day 15, months 3, 12, 18 and 24). Adverse events (AEs) were also recorded from medical records and hospital admissions and emergency department (ED) visits were analysed in order to identify suspected AEs. The adherence rate was calculated from pharmacy dispensing records. Results: 19 patients (68.4% women), mean age 61.9 (40–80) years with different forms of MS (relapsing remitting 26.3%, primary progressive 42.1% and secondary progressive 42.1%) were included. Effectiveness data are shown in Table 1 . 58.9% of patients (11/19) were hospitalised or visited the ED. The AEs identified were mostly urinary tract infections (37.3%) and dizziness, causing falls, (36.4%) (causal relationship not established). A high level of adherence (97.5%) was achieved. Conclusion: More than a half of the patients treated with fampridine experienced a clinically relevant improvement in walking ability (increase of over 20% in T25FW and MSWS-12 scale reduction ≥6), which was sustained for at least 24 months. Side effects were mild and acceptable. References and/or Acknowledgements: 1 Goodman AD, Brown TR, Krupp LB, et al . Sustained-release oral fampridine in multiple sclerosis: a randomised, double-blind, controlled trial. Lancet 2009;373:732–8 No conflict of interest.